2018
DOI: 10.3390/nano8121031
|View full text |Cite
|
Sign up to set email alerts
|

Nanoscale Ring-Shaped Conduction Channels with Memristive Behavior in BiFeO3 Nanodots

Abstract: Nanoscale ring-shaped conduction channels with memristive behavior have been observed in the BiFeO3 (BFO) nanodots prepared by the ion beam etching. At the hillside of each individual nanodot, a ring-shaped conduction channel is formed. Furthermore, the conduction channels exhibit memristive behavior, i.e., their resistances can be continuously tuned by the applied voltages. More specifically, a positive (negative) applied voltage reduces (increases) the resistance, and the resistance continuously varies as th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…This directly relates to different behaviors between anodic memristors thermally treated or formed in different electrolytes. It was previously reported that the switching mechanism may also refer to an electron trapping/detrapping from the Pt interface which can increase or lower the Schottky barrier, thus reducing or increasing the CFs conductance [ 49 ]. Additionally, in the present work, the CFs were influenced by electrolyte species incorporation.…”
Section: Resultsmentioning
confidence: 99%
“…This directly relates to different behaviors between anodic memristors thermally treated or formed in different electrolytes. It was previously reported that the switching mechanism may also refer to an electron trapping/detrapping from the Pt interface which can increase or lower the Schottky barrier, thus reducing or increasing the CFs conductance [ 49 ]. Additionally, in the present work, the CFs were influenced by electrolyte species incorporation.…”
Section: Resultsmentioning
confidence: 99%
“…With the extension of time, that is, the increase of pulse width, as a positive electric field is applied, the defect ions (positive V O s) in the film gradually enrich downward, resulting in the formation of a built-in electric field. 52,53 The direction of the built-in electric field is opposite to that of the external one, which weakens the size of the total electric field, as shown in Fig. 5(d).…”
Section: Centre-type Domains Created By Tip-fieldmentioning
confidence: 97%
“…[ 5,11,17–19 ] Furthermore, the study of the fabrication of BiFeO 3 (BFO) nanostructures with strain has shown that the eight polarization variants of the rhombohedral BFO cell, geometry constraints, and strain tuning are conducive to forming topological defects. [ 20–24 ]…”
Section: Introductionmentioning
confidence: 99%
“…[5,11,[17][18][19] Furthermore, the study of the fabrication of BiFeO 3 (BFO) nanostructures with strain has shown that the eight polarization variants of the rhombohedral BFO cell, geometry constraints, and strain tuning are conducive to forming topological defects. [20][21][22][23][24] However, quantitative experimental investigations of the exotic domain states are needed for smaller nanodots, which require piezoresponse force microscopy (PFM). PFM detects the local vibration of ferroelectric samples, which is caused by the application of AC voltage between an atomic force microscope (AFM) tip and the bottom electrode in a sample.…”
Section: Introductionmentioning
confidence: 99%